Of Ponzi schemes and investment scams - Mohd Sulaiman, Aiman Nariman; Moideen, Azza Isma; Moreira, Sharon David (Emerald Group Publishing Limited, 2016)
Purpose – This paper aims to chart the enforcement actions taken by the Malaysian regulatory authorities in relation to illegal investment schemes in Malaysia, and clarifies the various strategies adopted by the Malaysian regulatory authorities to ensure protection of investors in the capital market. The enforcement actions relate to the Swisscash scheme as well as commodities futures involving crude palm oil and a more recent case involving gold futures. These schemes share similar characteristics with Ponzi schemes that were thrust into the international limelight in the notorious Madoff Ponzi scheme and its allegation of regulatory failure. Design/methodology/approach – The paper clarifies, by way of case study, public enforcement of illegal investment schemes promoted through the Internet and schemes involving cross-border investments. Findings – The enforcement powers of the regulatory authorities in Malaysia are being utilized to ensure compliance with the law. The enforcement actions by the regulatory authorities in the afore-stated cases are significant in view of the successful custodial sentence of imprisonment, the regulators’ public enforcement action intended to compensate investors and the most recent case which is unfolding, due to the large number of alleged perpetrators and significant wealth transfer involved. Originality/value – Given the allegation of regulatory failure in other jurisdictions, this paper enables a view to be formulated of the timeliness and appropriateness of the enforcement actions.